2017
DOI: 10.1042/bcj20170340
|View full text |Cite
|
Sign up to set email alerts
|

Processing of syndecan-2 by matrix metalloproteinase-14 and effect of its cleavage on VEGF-induced tube formation of HUVECs

Abstract: Syndecans (SDCs) are transmembrane proteoglycans that are involved in cell adhesion and cell communication. Specifically, SDC2 plays a key role in tumorigenesis, metastasis, and angiogenesis. Previously, we found that rat SDC2 is shed by matrix metalloproteinase-7 (MMP-7) in colon cancer cells. Here, we analyzed the susceptibility of rat SDC2 to various MMPs. We found that the rat SDC2 ectodomain (ECD) fused to the C-terminal Fc region, which was expressed in mammalian cells, was cleaved more efficiently by MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 43 publications
1
13
0
1
Order By: Relevance
“…This was in line with the results conducted on 119 CRC patients where lower levels of circulating sEndoglin associated with a higher angiogenic activity [252]. More recently, Lee and co-authors, using a rat colonic cell line as a model, demonstrated that MT1-MMP was responsible for the degradation of the proteoglycan syndecan-2 [256]. Through its N-terminal domain, syndecan-2 selectively promotes a VEGFA-dependent neovascularization enhancing 6-O heparan sulfate chains' sulfation [257].…”
Section: Function Of Ecm Remodeling In Gi Tumor-associated Angiogenesissupporting
confidence: 81%
“…This was in line with the results conducted on 119 CRC patients where lower levels of circulating sEndoglin associated with a higher angiogenic activity [252]. More recently, Lee and co-authors, using a rat colonic cell line as a model, demonstrated that MT1-MMP was responsible for the degradation of the proteoglycan syndecan-2 [256]. Through its N-terminal domain, syndecan-2 selectively promotes a VEGFA-dependent neovascularization enhancing 6-O heparan sulfate chains' sulfation [257].…”
Section: Function Of Ecm Remodeling In Gi Tumor-associated Angiogenesissupporting
confidence: 81%
“…Syndecan ectodomain shedding is an important regulatory mechanism allowing for rapid changes in cell surface receptor dynamics; shedding occurs juxtamembrane and can be carried out by a number of matrix proteinases (Manon-Jensen et al, 2010). MMP7 and MMP14 are both able to shed the extracellular domain of syndecan-2, and MMP9 has been shown to shed syndecan-4 from the cell surface in response to TNFα (Kwon et al, 2014;Lee et al, 2017;Ramnath et al, 2014). There was a significant increase in MMP9 expression in ADAMTS-1 siRNA-treated cells, and upon loss of MMP9, via either an inhibitor or siRNA depletion, syndecan-4 was no longer lost from the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…A number of sheddases expressed on cell membranes, including MMPs and ADAM (a disintegrin and metalloprotease) metalloendopeptidases, are believed to cleave transmembrane molecules such as SDC and release their ectodomains [3,4]. Other proteases in the circulation, including secreted MMPs, plasmin and thrombin, have been shown to be able to further degrade the ectodomains into fragments [2,3,5].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, S2ED was also shown to be cleaved by MMP14 to produce multiple fragments. Moreover, the authors found that in cleaving S2ED, MMP14 impaired the ability of S2ED to decrease endothelial capillary-tube formation in vitro , which has implications in angiogenesis [4].…”
Section: Introductionmentioning
confidence: 99%